Determination of Sodium Chloride in Crude Oil of Gachsaran County Oil Wells - Hajian, R.; Oroojloo, A.H.; Mousavian, S.S.; Shams, N. (Asian Journal of Chemistry, 2011)
A new automated liquid-liquid extraction (LLE) apparatus have been designed and the applicability of this device was tested by the analysis of sodium chloride in crude oil of Gachsaran region in south of Iran. All of the results were compared with the standard test method. The advantages of this device include portability, water reservoir, cooling system, temperature controller and water level controller. The statistical test methods including t-test and F-test showed good accuracy and precision respectively in the analysis of sodium chloride in crude oils. The results showed that the mean of salt concentration as sodium chloride were 31.0 g m-3 with the relative standard deviation of (% RSD) 7.9 in Gachsaran county oil wells.